Kajian Proporsi Keterlibatan Perempuan (Gender) dalam Usaha Tani Padi di Kabupaten Bandung, Subang, dan Karawang - Sungkawa, Iwa (ComTech: Computer, Mathematics and Engineering Applications, 2014)
This study aimed to evaluate the involvement of women in Rice Farming Enterprise in Regency of Bandung, Subang and Karawang in a government program of gender equality. Through the estimation of proportion and descriptive studies by comparing figures targeted by the government of at least 30%, it can be evaluated that there is variability in all regencies. Further studies are analytical studies to determine the alleged intervals and hypothesis testing for proportions and to conduct studies by comparing observations and determined value by using the standard normal distribution. The results of the study shows that the role of women/gender in Rice Farming Enterprise is very dominant at each stage of planting, weeding and harvesting stages. For other stages such as land cultivation, Countermeasures Integrated Pest, irrigation and distribution, the women's role is less dominant. This information is expected to support the Agricultural Sector policy makersin developing women's empowerment and gender equity.